A Historical Review of Local Intermediaries in Impoverished Contexts. (September 2019) - Beninger, Stefanie; Shapiro, Stanley J.
The role of local intermediaries in impoverished contexts has been a focus of attention within the marketing and development literature since shortly after WWII. A systematic review of this work reveals that while much of this literature identifies market intermediaries as exploitative and unspecialized entities, other work views them more positively. These conflicting accounts, rarely supported empirically, have resulted in diverging policy recommendations. Many scholars call for the wholesale removal of such intermediaries, while a lesser number argue that they can and should be supported. The dominant view as regards local intermediaries reflects three prevailing biases in the marketing and development literature: an emphasis on transformation; a rejection of the local; and a favouring of consumers and producers over intermediaries. This paper describes these biases and proposes shaping constructs, potential future research questions, theoretical lenses, and methods of analysis that should ideally guide future scholarship on the role of local intermediaries within impoverished contexts.